Early in vivo discrimination of vulnerable atherosclerotic plaques that disrupt: A serial MRI study. (January 2016) - Pham, Tuan A.; Hua, Ning; Phinikaridou, Alkystis; Killiany, Ronald; Hamilton, James
Abstract: Background and aims: MRI has been validated as a suitable imaging modality for in vivo, non-invasive detection of atherosclerosis and has provided quantitative predictors of high-risk plaque. Here, we apply serial MRI to monitor the natural progression of plaques over a 3-month period in a rabbit model of atherothrombosis to determine differences over time between plaques that ultimately disrupt to form a luminal mural thrombus and plaques that remain stable. Methods: Atherosclerotic plaques were induced in 12 male New Zealand White (NZW) rabbits by aortic endothelial injury and a 1% cholesterol diet. The rabbits were imaged 5 times: at baseline, 1, 2, and 3 months, and 48hr after pharmacological triggering for plaque disruption. Results: Starting at 2 months, plaques that disrupted after triggering exhibited a higher remodeling ratio (RR, 1.05 ± 0.11 vs 0.97 ± 0.10, p = 0.0002) and a larger vessel wall area (VWA, 6.99 ± 1.54 mm 2 vs 6.30 ± 1.37 mm 2, p = 0.0072) than the stable non-disrupted plaques. The same trends were observed at 3 months: plaques that disrupted had a higher RR (1.04 ± 0.02 vs 0.99 ± 0.01, p = 0.0209), VWA (8.19 ± 2.69 mm 2 vs 6.81 ± 1.60 mm 2, p = 0.0001), and increased gadolinium uptake (75.51 ± 13.77% for disrupted vs 31.02 ± 6.45% for non-disrupted, p = 0.0022). Conclusions: MR images of plaques that disrupted revealed larger VWAs, RRs, and increased gadolinium uptake at 2 months and continued progression of these vulnerable features between 2 and 3 months. Non-disrupted plaques had an independent history without these hallmarks of vulnerability. Our results show that MRI can provide early detection of plaques at a higher-risk for luminal thrombosis. Highlights: Functional end point of plaque rupture is used in an atherosclerotic rabbit model. MRI can show differences in characteristics between stable and ruptured plaques. Plaques that disrupt develop vulnerable features while stable plaques do not.